A story of her own: memory and narrative in short fiction by Margaret Laurence, Alice Munro and Margaret Atwood (Cadernos de Letras da UFF, 2020)
The objective of this paper is to analyze the interplay of narrative, memory, and identity in short stories by Canadian authors Margaret Laurence, Alice Munro and Margaret Atwood. The three works explored in the article are narratives told from the perspective of characters who delve into their own past to make sense of their present, thereby revealing the strong bond between the act of remembering and the construction of one’s self.